2019
DOI: 10.1177/0363546519887749
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Demographic Factors Can Predict the Need for Primary Labral Reconstruction in Hip Arthroscopic Surgery: A Predictive Model Using 1398 Hips

Abstract: Background: Labral tears are the most common findings in patients with symptomatic femoroacetabular impingement (FAI). The restoration of labral function is critical, and labral reconstruction has been proposed as an alternative for irreparable tears. Purpose: To compare preoperative radiographic measurements and demographics of patients who underwent primary arthroscopic labral reconstruction versus primary labral repair and to identify factors that are predictive of the need for reconstruction. Study Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Moreover, these patients often have calcified labra that, with the addition of the required extensive acetabuloplasty, may require advanced labral restoration techniques. 39,42,68…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these patients often have calcified labra that, with the addition of the required extensive acetabuloplasty, may require advanced labral restoration techniques. 39,42,68…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated interrater reliability in measurements taken at the American Hip Institute. 25,42,65 All patients underwent magnetic resonance arthrography to assess labral tears and another potential extra- and intra-articular pathologies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a multivariate analysis, we identified radiographic and demographic preoperative factors and proposed a predictor model for labral arthroscopic reconstruction. This can be useful to surgeons in the early stages of the learning curve to anticipate the need for this complex procedure [ 40 ]. This study analyzed 18 variables in a cohort of 1398 primary hip arthroscopies (251 primary reconstructions and 1147 primary repairs) and found that the odds of labral reconstruction were 2.52 times higher in patients with Tönnis grade 1 than 0.…”
Section: Indicationsmentioning
confidence: 99%
“…39 The American Hip Institute's radiographic measurements have demonstrated good interobserver reliability in previously published studies. 19,42…”
Section: Imaging Protocolmentioning
confidence: 99%